L’influence des espaces de sociabilité sur la création en bande dessinée - Benjamin Caraco (Contextes)
As part of a research on the history of the authors of L’Association, we offer here a typology of their sociability spaces: art schools, workshops, fanzines, reviews and publishing houses. How do they give birth to a group? How do they influence creative and collaborative process between authors? Do they modify the ways knowledge and savoir-faires are passed from one generation on to another? In order to answer these questions, our article is based on a prosopography of the main authors from L’Association, relying on interviews. We primarily focus on workshops, which play a determinant part on these collaborative and emulative processes.